2012
DOI: 10.2319/083111-560.1
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution pattern in a root of maxillary central incisor having various root morphologies

Abstract: Objective: To investigate stress distribution in the roots of maxillary central incisors bearing various types of root morphologies with regard to application of different types of orthodontic forces using the finite element model (FEM). Materials and Methods: FEMs of maxillary central incisors with different root morphologies (normal, short, blunt, dilacerated, and pipette) were constructed, and orthodontic forces in various directions (intrusion, extrusion, tipping, and rotational) were applied to the tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
2
30
0
4
Order By: Relevance
“…Dilacerated roots as observed in the incisor root finite element models proposed by Kamble et al and Oyama et al[18,19] potentially led to an altered distribution of the stress when forces were applied to teeth during orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilacerated roots as observed in the incisor root finite element models proposed by Kamble et al and Oyama et al[18,19] potentially led to an altered distribution of the stress when forces were applied to teeth during orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic patients with sharp, pointed (triangle-shaped) roots that require premolar extraction, however, have a greater risk of severe root resorption[17]. Therefore, interest in variability in root morphology has increased recently[18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, the actual stress distribution pattern within the PDL plays an important role in the initiation of alveolar remodeling and resultant bone or root resorption. 51,52 Because of the stress distribution pattern within the PDL 52 in conjunction with the results on osteoclastic recruitment and cell cycle, 48,49 it may be indicated that certain time intervals are required for the cells to perceive stress alterations and respond with osteoclast activation and resorptive activity. Consecutively, buccopalatal alterations in force direction, as produced in this study by jiggling forces, could result in alternating loading and unloading conditions within the PDL, thus compensating for the destructive effects of continuous unidirectional forces in bone and subsequent root resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Ammar et al loaded forces with various magnitudes and directions to the mandibular left canine to study the stress in PDL and bone. Kamble et al applied orthodontic forces in various directions to the tooth axis at the bracket level to investigate stress distribution in the roots of maxillary central incisors. Jeon et al applied force at the center of the buccal crown surface of maxillary first molar to study the alveolar bone loss.…”
Section: Introductionmentioning
confidence: 99%